Cases and Materials : Decedents' estates and trusts - Ritchie, John; Alford, Neill H.;Effland, Richard W. (New York : The Foundation Press, Inc., 1982)
The primary purpose in integrating teaching materials on wills, trust and future interests was to prepare students for the private practice of probate and trust law.
Chapter 1. Introduction -- Chapter 2. General survey of administration and probate -- Chapter 3. Intestate succession -- Chapter 4. Limitations upon testamentary power -- Chapter 5. Execution wills -- Chapter 6. Revocation, revalidation and revival of wills -- Chapter 7. Contest of wills and related remedies -- Chapter 8. The private express trust -- Chapter 9. Trust litigation problems -- Chapter 10. Termination.
Includes index.
Keywords: DECEDENTS' ESTATES -- UNITED STATES -- CASES